Project Report on Advanced Flight Data Analysis System - JEENA JOY P, NISHITA B, NIVI N V and CHAYAN ROY (2010)
INTERNAL GUDIE : Mothi Bhavani V EXTERNAL GUIDE ; Brijish Singh USN NO : 1MJ07CS030 ,1MJ07CS053, 1MJ07CS055 and 1MJ07CS054 CARRIED OUT AT : Hindustan Aeronautics Limited Bangalore-560017 ACC NO : PR1808
Keywords: Data Analysis System